2000
DOI: 10.1037/0278-7393.26.6.1499
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of signal detection and threshold models of source memory.

Abstract: The authors analyzed source memory performance with an unequal-variance signal detection theory model and compared the findings with extant threshold (multinomial and dual-process) models. In 3 experiments, receiver operating characteristic (ROC) analyses of source discrimination revealed curvilinear functions, supporting the relative superiority of a continuous signal detection model when compared with a threshold model. This result has implications for both multinomial and dual-process models, bom of which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
160
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(174 citation statements)
references
References 39 publications
(89 reference statements)
11
160
3
Order By: Relevance
“…1 shows that words for which participants have stronger memory are also words for which they are likely to make correct source judgments. This finding has been reported for other item memory tasks and source memory tasks as well (18,19) and is consistent with the idea that item memory and source memory lie on a continuum of memory strength. Furthermore, in our study, the confidence ratings associated with forgotten words, item-only words, and item and source words were 2.04 Ϯ 0.09, 2.47 Ϯ 0.07, and 2.76 Ϯ 0.04, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…1 shows that words for which participants have stronger memory are also words for which they are likely to make correct source judgments. This finding has been reported for other item memory tasks and source memory tasks as well (18,19) and is consistent with the idea that item memory and source memory lie on a continuum of memory strength. Furthermore, in our study, the confidence ratings associated with forgotten words, item-only words, and item and source words were 2.04 Ϯ 0.09, 2.47 Ϯ 0.07, and 2.76 Ϯ 0.04, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…Slotnick et al (2000) also reported curvilinear source ROCs (pooled across old/new confidence ratings), albeit with a lesser degree of curvature than typically observed for item memory ROCs (see also Hilford et al, 2002). Although this flattening is problematic for the Gaussian assumption of SDT (Green & Swets, 1966), these results broadly support a model in which both item and source judgments are based on continuous processes.…”
supporting
confidence: 68%
“…1997, 1999). This preference is based on research in which confidence ratings for source memory were collected and used to compile so-called receiver-operating characteristic (ROC) functions (Glanzer et al, 2004;Hilford, Glanzer, Kim, & DeCarlo, 2002;Qin, Raye, Johnson, & Mitchell, 2001;Slotnick & Dodson, 2005;Slotnick, Klein, Dodson, & Shimamura, 2000;Yonelinas, 1999). The use of ROC functions is familiar from studies of item memory (for reviews, see Wixted, 2007;Yonelinas & Parks, 2007), in which discrete-state models predict linear ROCs (for binary response formats), whereas signal detection models predict curvilinear ones.…”
mentioning
confidence: 99%
“…With no correlation between recognition and source evidence, the model predicts that discriminability for unrecognized items should equal overall source discriminability (i.e., for recognized and unrecognized items) and should not change on the basis of the position of the recognition criterion. Previous research strongly suggests that recognition and source evidence values are correlated (DeCarlo, 2003;Slotnick & Dodson, 2005;Slotnick et al, 2000), so we do not seriously consider the no-correlation prediction.…”
Section: Notesmentioning
confidence: 99%
“…Recently, researchers have begun to explore models based on the continuous retrieval of source information, as opposed to the discrete state of source identification proposed by multinomial models (e.g., Banks, 2000;DeCarlo, 2003;Glanzer, Hilford, & Kim, 2004;Hilford, Glanzer, Kim, & DeCarlo, 2002;Qin, Raye, Johnson, & Mitchell, 2001;Slotnick & Dodson, 2005;Slotnick, Klein, Dodson, & Shimamura, 2000). Figure 2 displays the equal variance signal detection model for source discrimination based on continuous evidence (Wickens, 2002).…”
mentioning
confidence: 99%